Pembelajaran Pendidikan Agama Kristen Bagi Peserta Didik Non-Kristen di Pendidikan Umum Sukacita - Obet Nego; Debby Christ Mondolu (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2022)
In the Indonesian context, Christian education is commonly known as Christian Religious Education (PAK). It is generally understood that the implementation of PAK consists of teaching the Christian faith in the context of schools and tertiary institutions. The main goal of Christian Religious Education is to bring students to experience an encounter with Jesus Christ, then have a good relationship with God and be able to practice the truths of faith in everyday life. From understanding these goals, in fact PAK itself is holistic. Apart from emphasizing the knowledge aspect, other aspects such as spirituality, ethics, morals, and character must be present in the implementation of PAK in schools. The purpose of this research is to provide an understanding for non-Christian students to remain firm in their faith in the Lord Jesus, as well as to be role models in various aspects of life in the lives of students. This paper uses a qualitative approach, while the research method used is phenomenology. To obtain the data taken by means of interviews and by studying the literature. Because it uses literature studies, primary and secondary data collection techniques use library techniques and related literature. The data collection method or technique used in this paper is related book literature, through online libraries and literature in the form of e-books and articles/e-journals.